Physico-chemical aspects and applications of radiopharmaceuticals in nuclear medicine - Araújo, Daniel Lopes (2020)
This study aims to make an analysis of the physical and chemical characteristics of radiopharmaceuticals, as well as their applications in the method of nuclear medicine, through a literature review that selected 14 full papers, in English and Portuguese, published from 2016 to 2020. Radiopharmaceuticals are radioactive elements, which have in their internal composition a radionuclide and are used in Nuclear Medicine for diagnosis and therapy of various diseases. They have some very important characteristics to be chosen for use in the diagnostic imaging process, since these substances need to have a very short half-life to be used in the diagnostic clinic, other physical and chemical aspects must be analyzed such as decay mode (alpha, beta or gamma), energy emission and temperature and humidity conditions. They need to be prepared in accordance with strict standards of control and processing quality, so that you can ensure that the radiation doses the patient receives are minimal and the expected result is effective. There are several types of tests that use radioisotopes, such as PET-Scan, myocardial and pulmonary perfusion scintigraphy, renal scintigraphy, bone scintigraphy, among others. Therefore, the correlation existing between radiopharmaceuticals and nuclear medicine triggers an important step for the medical area in the current times, as it is capable of diagnosing complex diseases early using a low radiation level.